PENGEMBANGAN MODUL BERBASIS PROBLEM BASED LEARNING MATERI PERPINDAHAN KALOR MATA PELAJARAN IPA - Ani Khoirunnisa; Lukman Nulhakim; Ahmad Syachruroji (Profesi Pendidikan Dasar, 2020)
The purpose of this research is to develop a module based on problem based learning. This research was conducted at SDN Pegadingan 1 in the 5th grade Natural Sciences subject of heat transfer material contained in basic competencies 3.6. The method used in this research is a research and development method using research and development steps according to Sugiyono. Based on the feasibility test that has been conducted by a team of material experts, design experts, and education experts, an overall average score of 89.06% was obtained which included in the "Very Feasible" interpretation criteria, the average score of the material expert team's worth 89.20% which is included in the "Very Feasible" interpretation criteria, the design expert team's score was 79.48% which was included in the "Feasible" interpretation criteria, and the average score of education expert eligibility was 98.50% which was included in the "Very Feasible" interpretation criteria.